Necessity as a pretext for violation of Islamic commercial Law: a scenario of mortgage contract in the UK - Zakariyah, Luqman (Islami Bank Training and Research Academy, 2012)
This article attempts to examine some Islamic legal maxims in relation to the practice of mortgage in the UK. It looks at various products offered by either conventional banks or Islamic banks to determine whether necessity can be used as a pretext to breach the prohibition of riba. It answers, in light of maqasid al-shari‘ah (the spirits of Islamic law) through these legal maxims, the argument of those who condemn outright the “halality” of the current products of Islamic mortgage and suggest an amenable solution. The paper traces the development of Islamic mortgage in Britain and the involvement of Muslims in this development. It further exposes the principle of necessity in Islamic law and its role in relieving its adherent from hardship. The paper then argues that if provision is a settled rule in Islamic law, application of it to the present situation of Muslims in Britain is inevitable.The effect of refrainment of Muslims from participation in the current global economy, especially, property investment particularly in the West at large, will put Muslims in the desecration of wealth.